Analisis Integrasi Nilai Kearifan Lokal dalam Pembelajaran Pendidikan Agama Islam - Fajriah Inayati; Opik Taufik Kurahman; Dadan Rusmana (Pusat Riset dan Inovasi Nasional, 2024)
Integration of local wisdom values in Islamic Religious Education learning is a systematic effort to combine local wisdom values with the principles of Islamic teachings. This study aims to analyze efforts or methods used in integrating local wisdom in Islamic Religious Education learning. The method in this study uses library research involving the collection, analysis, and synthesis of data from various sources that have been obtained. The sources used are written sources such as scientific journals and relevant scientific articles. The results of the study revealed that the integration of local wisdom values in Islamic Religious Education learning is carried out through through curriculum development, addition of teaching materials, and attention to the learning methods applied. The success of this integration is highly dependent on the collaborative role between teachers, students, local communities, and cultural experts in creating meaningful learning experiences.